(untitled) (American Journal of Pedagogical and Educational Research, 2025)
The article examines the theoretical and practical aspects of inclusive education in the preschool education and training system. Particular attention is paid to the adaptation of the educational environment in accordance with the needs of children with disabilities and other special educational needs. The principles, conditions and models of inclusive practice in early childhood are highlighted. Effective methods and technologies of support are revealed. The importance of interdisciplinary interaction and professional training of teachers for the successful implementation of the inclusive approach is emphasized.